PENGARUH INFORMASI BERLEBIHAN TERHADAP KEPUTUSAN PEMBELIAN BARANG IMPOR E-COMMERCE DENGAN FISKAL IMPORT BARRIER SEBAGAI VARIABEL MODERASI: PERSPEKTIF MODEL HEURISTIK-SISTEMATIS - Yusuf, Himawan; Wahyudi, Imam Tri (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
This research aims to examine the influence of excessive information on purchasing decisions for imported goods via e-commerce with the fiscal import barrier variable as a moderating variable. The data analysis method in this research is Structural Equation Modeling using Smart PLS 3.0 software. Sample selection used the purposive sampling method. Based on the results and discussion, the moderating effect of the fiscal import barrier does not have a significant effect on purchasing decisions. This can be influenced by the background of respondents who have middle to upper income levels, so that the burden of paying import duties does not strengthen or weaken respondents' intentions to buy imported goods via e-commerce. The novelty of this research is the use of the fiscal import barrier variable as a moderating variable for purchasing decisions, which is something new.